PENERAPAN ILMU FILSAFAT DALAM MEMBANGUN POLA PIKIR SISWA DALAM MERESPON PEMBELAJARAN PADA KURIKULUM MERDEKA - Rena Elia; Yeni Erita; Desyandri (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2022)
The purpose of this research is to see the effectiveness and how important philosophy is in stimulating students' mindsets in responding to information about science in independent curriculum learning based on the times. The method used in carrying out this research is library research using a qualitative approach, namely an approach taken by processing data by presenting data through a review of thoughts, expert opinions or information related to research problems in the form of books. as well as previous research that is able to support the discussion of the issues raised. The results of research conducted cognitively found that the application of philosophy in learning will produce a positive contribution that logically will be able to train students in forming a critical mindset in responding to information both informatively and theoretically. In the development of an independent curriculum learning model it will be able to trigger students to respond to science based on active logic.